تقييم أداء هوائي LPDA عريض الحزمة ومقارنته بهوائي نصف طول الموجة عند تغير التردد - يونس, معين; يوسف, عزيز (Latakia University Journal -Engineering Sciences Series, 2018)
أصبحت الهوائيات في الوقت الحاضر حاجة أساسية لا غنى عنها وخصوصاً في مجال الشبكات اللاسلكية, وتطورت في العقود القليلة الماضية بشكل كبير جداً من حيث الربح والممانعة وعرض الحزمة وعرض المجال الترددي وشكل المخطط الاشعاعي وغير ذلك بما يتناسب مع المتطلبات الجديدة والمتزايدة. تم الاهتمام في هذا بدراسة هوائي عريض الحزمة حيث يكون هذا الهوائي مهماً جداً في الأنظمة التي تعمل على مجموعة من الترددات وليس على تردد ثابت حيث ان الهوائيات التقليدية التي يتم تصميمها على تردد محدد تتغير استجابتها بشكل ملحوظ اذا ما استخدمت على مجال ترددي عريض حول التردد المصممة لأجله. تم في هذا البحث تصميم الهوائي LPDA (Log periodic Dipole Array) عريض الحزمة ودراسة سلوكه على مجال ترددي عريض ومقارنته بالهوائي المرجعي للهوائيات السلكية وهو هوائي نصف طول الموجة وتم التركيز على دراسة تأثير تغير التردد على شكل المخطط الاشعاعي للهوائي وعرض حزمة الاشعاع عند مستوي نصف الاستطاعة وعلى نسبة الأمام الى الخلف (F-B). Antennas have become an indispensable basic need, especially in the area of wireless networks, and have developed in the past few decades in a very large way in terms of profit and resistance, bandwidth, bandwidth, radiation pattern, etc. in line with new and increasing requirements. In this study, we are interested in studying a broad band antenna where this antenna is very important in systems that operate on a set of frequencies rather than at a fixed frequency. The traditional antennas that are designed at a specific frequency change their response significantly if used on a wide bandwidth around the designed frequency In this study, the LPDA (Log periodic dipole Array) antenna was designed and studied in a broadband field and compared to the antenna reference of wire antennas. It is a half-wavelength antenna λ/2. The study of the effect of frequency change in the antenna radiation pattern and the radiation beam Half-power level and front-to-back ratio (F/B).